Protein traffic in parasites and mammalian cells. Proceedings of a workshop - Lonsdale-Eccles, J.C.; Lenahan, J.K. (International Laboratory for Research on Animal Diseases, 1989)
The International Laboratory for Research on Animal Diseases (ILRAD) has recently developed interests in several areas of cell biology and biochemistry that are relevant to trypanosomiasis and theileriosis (East Coast Fever (ECF)). The reasons for this interest stem from a perceived difficulty of tackling trypanosomiasis by conventional vaccination procedures due to the tremendous antigenic variation that trypanosomes can undergo. Thus approaches other than a purely immunological one are now being explored. As a part of this new emphasis, this workshop was held to review the current state of knowledge in the field of protein traffic and catabolism and to attempt to address these issues, with particular reference to parasitic diseases. The topics covered include such areas as protein targeting, protein assembly, protein degradation, endocytosis and lysosomal activity.